CONTAMINACIÓN SONORA Y PERCEPCIÓN DEL APRENDIZAJE - SANCHEZ GARCIA, Tula (2021)
Sound pollution has implications for student learning and causes a very harmful effect in noisy environments, especially academic performance; is that noise has the capacity to unintentionally attract our attention and, therefore, it is disruptive in relation to the tasks that we may be performing at a given moment. Among the negative effects, in addition to attention deficit, increase in the error rate, imprecisionand lack of quality in the responses issued, general states of anxiety and overall feeling of tiredness, which cause them concerns and alter communication, such a factor are  impact noises such as horn, transport leaks, street propaganda. Productivity is given in inverse function to the noise that is around, that is, the higher the noise, the lower the performance of a person. Inside the ear, there are auditory sensory cells no larger than 18 thousand in each ear, and they lose their capacity for renewal due to too loud sounds, and it is a shame since the other sensory cells such as those of the tongue, nose and eye , which are constantly being renewed.